The Analysis of Service Disciplines of Differentiated Services Flows - Dekeris, B.; Narbutaitė, L.; Adomkus, T. (Elektronika ir Elektrotechnika, 2004)
Currently the most relevant problem is how to improve the quality of service in IP networks. In order to secure proper quality of service, the network must react adequately to the service generated load, intended to the network and contribute proper amount of resources. In this paper we analyze the quality assurance of multiple services in IP network using differentiated services. We introduce the analytical differentiated flow service model in the router and propose assumptions to evaluate the different queuing disciplines in this paper. In the differentiated services network the classification particularity of complex flow is reflected by the management of queues. Therefore the imitation model was constructed which allows to evaluate different disciplines which serve queues for three priorities flows. There was estimated the intensity effect of different class services to analyzing classes of flows delays using FIFO, PQ, CBQ and WFQ disciplines. Ill. 14, bibl. 7 (in Lithuanian; summary in Lithuanian, English, Russian).